Pengaruh Kualitas Produk, Harga dan Ulasan Konsumen Terhadap Keputusan Pembelian Produk Skintific di Kalangan Generasi Z(Survei Pada Mahasiswa Universitas Slamet Riyadi Surakarta) - Videllia Chitra Ananda Sukarno; Retno Susanti (Teewan Journal Solutions, 2025)
This research aims to analyze the significance of the influence of product quality, price and consumer reviews on purchasing decisions for Skintific products among generation Z. The types of data used in this research are quantitative and qualitative data. The data sources used are primary and secondary data. The sample in this research was 100 students at Slamet Riyadi University, Surakarta. The method used in sampling was purposive sampling with the characteristics of consumers who were aged 17-25 years and were active UNISRI students and had purchased Skintific products at least once. Data collection techniques in this research used questionnaires and literature study. Test the research instrument using validity and reliability tests. The classical assumption test uses tests: multicollinearity, autocorrelation, heteroscedasticity and normality. Data analysis techniques use multiple linear regression tests, t tests, F tests and R2. The results of the validity and reliability tests show that all statements regarding the variables of product quality, price and consumer reviews and purchasing decisions are declared valid because the p-value is < 0.05 and reliable because the Cronbach's alpha value is > 0.60. The results of the classical assumption test show that all variables have passed the multicollinearity, heteroscedasticity, autocorrelation and residual normal distribution tests. The results of the regression analysis obtained the equation Y = 4.205 + 0.205 X1 + 0.390 X2 + 0.488 X3. The results of the t test show that product quality (X1) has no significant effect on the decision to purchase Skintific products among generation Z, price (X2) and consumer reviews (X3) have a significant effect on the decision to purchase Skintific products among generation Z. The results of the F test show that the regression model used in this research is correct. The R2 test results show that the contribution of the independent variable to the dependent variable is 40.3%, the remaining 59.7% is influenced by other factors outside the variables studied.